Purification and characterization of phytase from Klebsiella pneumoniae 9-3B - Lotis Escobin-Mopera (2018)
Phytase, an enzyme that catalyzes the hydrolysis of phytate, was purified from Klebsiella pneumoniae 9-3B. The isolate was preferentially selected in a medium which contains phytate as a sole carbon and phosphate source. Phytic acid was utilized for growth and consequently stimulated phytase production. Phytase production was detected throughout growth and the highest phytase production was observed at the onset of stationary phase. The purification scheme including ion exchange chromatography and gel filtration resulted in a 240 and 2077 fold purification of the enzyme with 2% and 15% recovery of the total activity for liberation of inorganic phosphate and inositol, respectively. The purified phytase was a monomeric protein with an estimated molecular weight of 45kDa based on size exclusion chromatography and SDS-PAGE analyses. The phytase has an optimum pH of 4.0 and optimum temperature of 50°C. The phytase activity was slightly stimulated by Ca 2+ and EDTA and inhibited by Zn 2+ and Fe 2+ . The phytase exhibited broad substrate specificity and the K m value for phytate was 0.04mM. The enzyme completely hydrolyzed myo-inositol hexakisphosphate (phytate) to myo-inositol and inorganic phosphate. The properties of the enzyme prove that it is a good candidate for the hydrolysis of phytate for industrial applications. © 2011 The Society for Biotechnology, Japan.